A Supplementary Note on Complete Ordering and Revealed Preference - Newman, Peter (Review of Economic Studies, 1960)
A Supplementary Note on Complete Ordering and Revealed Preference Peter Newman Peter Newman Jamaica Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 3, June 1960, Pages 202–205, https://doi.org/10.2307/2296082 Published: 01 June 1960